Long Non-Coding RNA H19 Participates in Periodontal Inflammation via Activation of Autophagy - Guo R; Huang Y; Liu H; Zheng Y; Jia L; Li W (Dove Medical Press, 2020)
Runzhi Guo,1 Yiping Huang,1 Hao Liu,1 Yunfei Zheng,1 Lingfei Jia,2 Weiran Li1,3 1Department of Orthodontics, Peking University School and Hospital of Stomatology, Beijing 100081, People’s Republic of China; 2Central Laboratory, Peking University School and Hospital of Stomatology, Beijing 100081, People’s Republic of China; 3National Engineering Laboratory for Digital and Material Technology of Stomatology, Beijing Key Laboratory of Digital Stomatology, Beijing 100081, People’s Republic of ChinaCorrespondence: Yiping Huang Department of OrthodonticsPeking University School and Hospital of Stomatology, 22 Zhongguancun Avenue South, Haidian District, Beijing 100081, People’s Republic of ChinaTel/ Fax +86-10-82195775Email hyp891213@163.comWeiran LiDepartment of Orthodontics, Peking University School and Hospital of Stomatology, 22 Zhongguancun South Avenue, Haidian District, Beijing 100081, People’s Republic of ChinaTel/ Fax +86-10-82195332Email weiranli@bjmu.edu.cnPurpose: Periodontitis is the leading cause of tooth loss. The role of long non-coding RNA (lncRNA) in periodontal inflammation remains unclear. The aim of this study was to investigate the role of lncRNA H19 in periodontitis and its possible regulation of autophagy in periodontitis.Material and Methods: Inflammation level was determined by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) in periodontal ligament cells (PDLCs). Western blotting, flow cytometric analysis, and immunofluorescence staining were used to detect the autophagy flux. Overexpression or knockdown of H19 was used to confirm its function. Ligature-induced periodontitis model in mice and periodontitis-affected human gingival tissue were used in vivo. RNA sequencing was performed to determine the differentially expressed genes.Results: Autophagy was significantly increased in PDLCs after inflammatory stimulation as well as in a ligature-induced periodontitis model in mice and periodontitis-affected human gingival tissue. During the inflammatory process, H19 expression was also significantly upregulated. Further, the levels of autophagic markers were significantly upregulated after overexpressing H19 in PDLCs, and the increased autophagic activity induced by inflammatory stimulation was reversed by H19 knockdown. RNA sequencing showed that the expression profiles of mRNAs were significantly altered after H19 overexpression, and the differentially expressed genes were enriched in the PI3K/AKT signaling pathway, which was confirmed by the decreased p-AKT protein expression in the H19 overexpression group.Conclusion: Periodontal inflammation activates autophagy flux, and H19 mediates the activation of autophagy via AKT pathway in periodontitis. This study expands our understanding of molecular regulation in periodontitis.Keywords: autophagy, periodontitis, long non-coding RNA